Life & Work In Medieval Europe. - Boissonnade (Taylor and Francis, 2013)
This is an attempt to construct an ordered synthesis of the evolution of labor in Christian Europe during the Middle Ages. Its aim is not only to analyze the variations in the legal status of persons and of lands, but above all to set the working classes in the historical framework in which they lived, to trace the reciprocal action of political and social institutions, of exchange, of industrial and agricultural production, of the colonization of the soil, of the distribution of landed and movable wealth, upon those economic transformations which brought about the appearance of new forms of l.